Albuminuria and retinal vessel density in diabetes without diabetic retinopathy: the Kailuan Eye Study - Wang, Qian; Liu, Lili; Jonas, Jost B.; Gao, Bixia; Wu, Shou Ling; Chen, Shuo Hua; Yan, Yan Ni; Yang, Jing Yan; Zhou, Wen Jia; Yang, Mo Chi; Chan, Szy Yann; Zhang, Luxia; et al. (Acta ophthalmologica, 2021)
Background Diabetic retinopathy and chronic kidney disease are both major complications of diabetes mellitus. We explored the relationship between retinal vessel density (VD) and albuminuria in diabetic patients without conventionally defined diabetic retinopathy. Methods The cross-sectional community-based Kailuan Diabetic Retinopathy Study included patients with type 2 diabetes without diabetic retinopathy who participated in the community-based longitudinal Kailuan study and who had undergone ocular fundus photography, kidney function assessment, and optical coherence tomographic angiography (OCT-angiography) for the assessment the retinal perfusion density (PD) and retinal VD. Results The study included 447 patients (mean age: 60.9 ± 9.7 years). Higher PD and VD were associated with a lower urinary albumin-creatinine ratio (uACR) (macular region: p = 0.007: standardized regression coefficient beta: −0.14; and p = 0.008, beta: −0.13, respectively; parafoveal region: p = 0.006, beta: −0.14; and p = 0.007, beta: −0.14, respectively) after adjusting for age and ocular axial length. In a reverse manner, higher uACR was associated with lower PD and VD (macular region: p = 0.009, beta: −0.14; and p = 0.01, beta: −0.14, respectively; parafoveal region: p = 0.008, beta: −0.14; and p = 0.01, beta: −0.14, respectively), after adjusting for diabetes duration, blood pressure, serum concentration of C-reactive protein and high-density lipoprotein cholesterol and ocular axial length. In a multivariable model, the prevalence of macroalbuminuria increased by 11% (95% CI: 2%, 18%) and 17% (95% CI: 3%, 30%), respectively, for each mm−1 decrease in VD and each unit decrease in PD. Conclusions and Relevance After adjusting for systemic and ocular parameters, diabetic patients without diabetic retinopathy showed a reduction in OCT-angiographic retinal vascular measurements in association with systemic parameters indicating chronic kidney disease. Optical coherence tomographic (OCT)-angiographic retinal microvascular parameters may serve as markers for chronic kidney disease.
First published: 23 December 2020
Gesehen am 20.11.2023